The Emergence Of Green Logistics For International Sustainable Development: A New Management Levers. (International Journal of Environmental Sciences, 2025)
Logistics has become a strategic issue for all companies, regardless of the sector in which they operate. Strong competition and globalization have prompted organizations to do everything in their power to optimize their supply chain. To this end, economic, environmental and social constraints are driving companies to be constantly on the lookout for new developments, whether technological and/or organizational. Green logistics has become a crucial component of sustainability in the logistics services sector. This study looks at how international logistics service providers are integrating green logistics principles into their operations, in line with the green logistics charter. This research explores the scope and effectiveness of the commitments made by these companies. Through this exploration, we have assessed the green logistics practices adopted and their impact on development performance. The main objective of this contribution is to attempt to clarify the basic concepts of Green logistics and sustainable development.